Plant Thorn Synovitis of the Hand in an Adult Patient: A Case Report and Review of the Current Literature. (24th September 2019) - Zhu, Sarah L.; Leveille, Cameron F.; Dunn, Emily E.; Cooper, Michael J.
This is a case of plant thorn synovitis of the hand in an adult following a plum tree thorn injury, the first reported case in the hands in the past decade. The patient initially presented with persistent joint discomfort following removal of a retained plum thorn fragment from the skin overlyin the proximal interphalangeal joint of the left middle finger. Initial radiography and sonography imaging following the removal revealed no foreign bodies. However, the patient's symptoms were worsening and refractory to anti-inflammatory and antibiotic treatment. An exploratory surgery was carried out, which revealed multiple plant thorn fragments within the synovium, each measuring approximately 1 mm in size. A synovectomy was performed and the patient recovered with full function. Our case of plant thorn synovitis is discussed along with a review of the current literature on plant thorn synovitis in the hands.